A Spatial Analysis of the Italian Second Republic, Second Version - LANDI, Massimiliano (Institutional Knowledge at Singapore Management University, 2012)
We apply the Optimal Classification method to a newly created dataset to provide a spatial map of the Italian Second Republic (1996-2008). We find a bi-dimensional political space in the XIII Legislature and virtually a one dimensional political space in the XIV and XV Legislatures. In addition, the main dimension is explained along the dimension government opposition rather than on the traditional left and right dimension. During the Second Republic, Italy experienced changes in electoral system and in the format of the parties. We use our data to discuss the implications of either change on the dimensionality space. We find that the format of the party system was a more important determinant of the dimensionality of the political space than changes in the electoral system.